PELABELAN GRACEFUL, SKOLEM GRACEFUL DAN PELABELAN ???? PADA GRAF H-BINTANG DAN A-BINTANG - Nurul Huda; Zulfi Amri (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2012)
The graph G = (V, E) is the ordered set of sets in which V is the set null node and E is a set of arcs. Labeling on graph G is determination of node and arc values or both with certain rules. Labeling graceful is the α α function of the set of vertices V to the set of numbers 0.1,2, .... ???? which induces the α 's bijtive function of the set of arc E to the set number 1,2, .... ???? where each arc uv ∈ E with node u, v ∈ V apply α '(uv) = α (????) - α (????). The graceful grid labeling is a modification of graceful labeling ie the injection function μ from the set of vertices V to the set of numbers 1,2, .... ???? yang induces the μj 's bijtive function of the arc set E to the set of numbers 1,2, .... ???? where each arc uv ∈ E with node u, v ∈ V apply μ '(uv) = μ (????) - μ (????). Labeling ρ is another modification of graceful labeling that is the γ injection function of the set of vertices V to the set of numbers 0.1, 2, .... ???? + 1 which induces the function bitif γ 'from the set of arc E to set of numbers 1,2, .... ???? where each arc uv ∈ E with node u, v ∈ V apply γ '(uv) = γ (????) - γ (????). The H-star chart is formed of the letter H and all its leaves are given a star graph ????????. A-star chart formed from letter A and all its leaves are given a star graph ????????. In this paper is given graceful label construction, graceful scheme and labeling ρ for H-star graphs A-star.